Professional Zakat and Its Relevance to Theory Maslahah Muhammad Sa’id Ramadhan Al-Buthi - Akbar, Ali; Rizki, Muh (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Zakat is an Islamic obligation, one of the five pillars of Islam. In early Islam, zakat focused on existing community income, such as agriculture, animal husbandry, and trade. However, in modern times, income sources have increased, including new professions such as government employees, lecturers, doctors, and so on. Therefore, it is necessary to discuss zakat on income from these professions. The purpose of this study is to explain the definition of professional zakat, how it is calculated, compare the perspectives of classical and contemporary scholars on professional zakat, and assess its relevance to the theory of mashlahah proposed by Dr. Muhammad Sa'id Ramadhan Al-Buthi. This research is a library research with a qualitative approach, where the primary data is the book of fiqh zakat by Al-Qardhawi and Fikh Al-Islam Wa Adillatuhu by Wahbah Az-Zuhaili, the secondary data comes from journal articles that are in accordance with the research. The data collection technique is by identifying appropriate data, then reviewing and identifying it, then analyzing it by interpreting it in depth and presenting it in the research. The results of this study are professional zakat is a mandatory zakat imposed on everyone who earns income from each of their businesses with the condition that it reaches 85 grams of gold if the income is calculated in one year, professional zakat is relevant to the Al-Buthi mahslahah because it is based on Maqasid Syari'ah and does not conflict with the Qur'an, Sunnah, qiyas and other maslahah.